2014
DOI: 10.1186/1471-2458-14-1307
|View full text |Cite
|
Sign up to set email alerts
|

Identifying associations between sedentary time and cardio-metabolic risk factors in working adults using objective and subjective measures: a cross-sectional analysis

Abstract: BackgroundSedentary behavior has been reported to be associated with metabolic and vascular health independent of moderate-to-vigorous physical activity (MVPA). In order to select appropriate options to measure sedentary behavior in practice and research settings, it is worthwhile to characterize the extent to which objective and subjective measures of sedentary behavior quantify adverse health risks in the same population. This cross-sectional analysis compared accelerometer-derived and self-reported sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 41 publications
(50 reference statements)
7
60
4
Order By: Relevance
“…Similar to our findings, other studies have reported significant associations of SB with poor lipid profiles and non-significant associations between SB and blood pressure [34]. It appears, based on the results observed in this review and other studies, SB may have a stronger influence on blood lipids than blood pressure, although more research is needed to confirm this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our findings, other studies have reported significant associations of SB with poor lipid profiles and non-significant associations between SB and blood pressure [34]. It appears, based on the results observed in this review and other studies, SB may have a stronger influence on blood lipids than blood pressure, although more research is needed to confirm this finding.…”
Section: Discussionsupporting
confidence: 89%
“…After reviewing their titles and abstracts, a total of 63 articles were excluded because of the following reasons: not reporting sedentary behavior (n = 22), special or patient populations (n = 16), incorporating children as subjects (n = 9), studies not conducted in Japan (n = 5), individual calibration or validation studies of wearable devices (n = 4), non-human subjects (n = 3), non-English articles (n = 2), and review or protocol articles (n = 2). The characteristics of the seven articles [22][23][24][25][26][27][28] that met the inclusion criteria are summarized in Table 2. Since this systematic review is based on a search done on a single database (the PubMed), caution should be observed in terms of comprehensiveness.…”
Section: A Systematic Review On Sedentary Behavior Assessments In Japanmentioning
confidence: 99%
“…Of the seven articles reviewed in this study, 6 adopted the waist-worn Active style Pro tri-axial accelerometer [22][23][24][25][26][27] . The remaining article reported on the thighworn activPAL to develop and test an occupational sitting questionnaire 28) .…”
Section: A Systematic Review On Sedentary Behavior Assessments In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…3). [7][8][9] Variations in time spent in sedentary and PA can be between 20% and 40% depending on the level of occupational PA. Workers in low PA professions such as technical/professional office work, research and development, teaching profession, and finance are at an increased risk of engaging in prolonged sitting at work. 10 However, current workplace wellness programs have primarily focused on promoting MVPA, 11,12 which is associated with substantial health benefits.…”
mentioning
confidence: 99%